Punitive Sanctions and the Transition Rate from Welfare to Work - van den Berg, Gerard J.; van der Klaauw, Bas; van Ours, Jan C. (Journal of Labor Economics, 2004)
In the Netherlands, the average exit rate out of welfare is dramatically low. Most welfare recipients have to comply with guidelines on job search effort that are imposed by the welfare agency. If they do not, then a sanction in the form of a temporary benefit reduction can be imposed. This article investigates the effect of such sanctions on the transition rate from welfare to work using a unique set of rich register data on welfare recipients. We find that the imposition of sanctions substantially increases the individual transition rate from welfare to work.